Portuguese Cultural Studies/Cultural Studies in Portugal: Some Thoughts on the Making and Remaking of a Field - Sampaio, S. (2013)
This article discusses the overall situation of cultural studies in Portugal. It starts by analysing some of the courses and graduate programmes currently on offer. The results suggest that cultural studies is experiencing a fast academic expansion. While this seems to be entangled with top-down institutional changes, in the wake of the Bologna process and the turn to the cultural/ creative industries and as part of a more general shift to the ‘new economy’, there are reasons to believe that al-ternative understandings of cultural studies have not died out. The name ‘cultural studies’ continues to cause unease in some academic quarters (namely, in literary studies) and there is ambiguity regarding what is meant by it. Cautioning against the tendency to reduce Portuguese cultural studies to a straightforward import from the Anglophone world, I argue for the need to conduct historically informed research on local strands and traditions of cultural theory and critique. I conclude that only a combined synchronic and diachronic approach – one that is sensitive to national and transnational contexts and intersections – will allow us to gain a bet-ter understanding of the deep-running contradictions that characterise the field, helping us to clarify the stakes and reconnect to a socially relevant and critique-orientated intellectual project.